KAJIAN VISUAL KARTUN KONPOPILAN - I Wayan Nuriarta (Prasi: Jurnal Bahasa, Seni, dan Pengajarannya, 2017)
To bring humor or social criticism, a cartoon on newspapers usually uses two kinds of text, such as visual text and verbal text. Both of them are reinforcing the message that delivered by the cartoonist, either humor or criticism. If one of these texts does not exist, the message will be very difficult to understand as they need each other.  Konpopilan cartoon is published in Kompas newspaper every Sunday is different. This cartoon firmly states ‘itself’ is a work of visual communication. That background study brought this research has some objectives, such as; (a) To describe the visual language that the Konpopilan cartoons were published in Kompas Newspaper in 2016, (b) To describe the meaning of denotation and connotation of Konpopilan cartoons in Kompas newspaper in 2016. This research used Qualitative research. The results of this research shown that the visualization of Kompopilan cartoons are a man who wears traditional woven bamboo hat and animals. This research uses visual language as it mean discussion. Cara Wimba uses very long shot, long shot, and medium long shot, Tata Ungkap Dalam uses normal perspective, Tata Ungkap Luar is not presented in 1 frame cartoon style but presented by strip comic that uses more than one frame. Denotation meaning of this cartoon is described by the person who wears a traditional woven bamboo hat and some animals that has connotation meaning as a cartoon focusing on social criticsm; how human being should take care of the environment and anti corruption.